The joint role of school adaptation and physical activity in the nonlinear effect of adolescent self-control and mental health - Yueyan Jiang; Chong Liu; Jun Yan; Lingzhi Wang (Scientific Reports)
Abstract To examine the nonlinear effects of adolescent self-control on mental health and investigate the mediating role of school adaptation and the moderating role of physical activity, we conducted psychological measurements on 2077 high school students from eight different schools using a psychological scale. The results revealed a U-shaped relationship between adolescent self-control and their mental health and school adaptation, with school adaptation mediating this relationship. Furthermore, physical activity was identified as a regulator of the indirect effects of self-control on mental health through school adaptation. This suggests that adolescents sometimes need to balance their focus between internal self-control and external adaptation strategies to succeed in school. This balancing act can lead to an overuse of self-control resources, resulting in "excessive adaptation," which negatively impacts their mental health. However, physical activity can help mitigate these negative effects by moderating the relationship between school adaptation and mental health. The study underscores the importance of balancing self-control and school adaptation in adolescents. It recommends that educators incorporate physical activity into routines to help maintain adolescents’ mental health.